Բացառիկ առաքելություն կամ խիզախման փիլիսոփայությունը - Հակոբյան, Վարդան («Դիզակ պլյուս» հրատարակչություն)
В статье представлена литературная и общественная характеристика деятельности одного из достойных сынов Арцаха, поэта, общественного деятеля Григора Нерсисяна, жившего и творившего в начале 20 века. Выдвигается проблема целостной публикации его литературного наследия. The article presents the literary and social characterestics of the activity of one of the worthy sons of Artsakh, a poet and a public figure Grigor Nersisyan, who lived and created at the begining of the 20th century. The problem of an integral publication of his literary heritage is put forward.
Keywords: Փիլիսոփայություն